A Note on the Low Income-Inequality Miracle in Taiwan (1976-1997) - Rao, V.V. Bhanoji; Mukhopadhaya, Pundarik (Journal of Income Distribution®, 2001)
Within the context of globalization and openness of the Taiwan economy, the Gini ratio for income distribution among individuals remained within a narrow range of just 0.35-0.36 for as long as two decades. The low level as well as the constancy of the degree of inequality, data availability from household surveys on an annual basis, the very swift publication of the survey reports and the high degree of agreement between the survey and national accounts-based aggregated income constitute a “miracle” as far as the experience of developing countries go.